P761Antibody mediated rejection related with CMV and EBV infection in heart transplants recipients: a possible relation with infection and complement activation. (15th July 2014) - Fedrigo, M; Abate, D; Sgarabotto, D; Feltrin, G; Castellani, C; Gambino, A; Gerosa, G; Valente, M; Thiene, G; Angelini, A
Abstract: Aim: Aim of the present study was to investigate the relationship between CMV and EBV infection and the occurrence of antibody mediated rejection (AMR) in a cohort of adult heart transplant recipients (HTXs). Materials and Methods: 47 adult HTX patients were enrolled in a case-control study from June 2010 to June 2012, 24 of them with humoral rejection and 23 without. Endomyocardial biopsies (EMBs) were routinely performed and pathological diagnosis of AMR assessed according to ISHLT 2011. Donor specific antibodies titles were evaluated at the same time of EMBs biopsy. Routine surveillance for viral reactivation or infection comprised weekly determination of whole blood CMV DNAemia during the first 100 days post-transplant. CMV and EBV DNAemia was evaluated using real-time PCR. We divided the cohort study in two groups according to time since HTx as early (1-90 days) and late (91-360 days). Results: In the AMR group the EBV infection was present in 13 cases (13/24, 54%) and CMV in 10 cases (10/24, 42%). In the control group the cases of pts with EBV were 2/23 (9%), while CMV were 4/23 (17%). In the early period EBV infection was present in 12/24 cases (50%, p=0.000) and CMV infection was present in 10/23 cases (p=0.042). In the late period EBV was present in 6/24 cases (25%, p=0.002) and CMV in 1/23 (4%, p=0.000). Conclusions: EBV and CMV infections during follow-up post heart transplantation occurred more frequently in patients with AMR suggesting that virus could act as a trigger in humoral rejection.